DIALOGUE SPEECH IN ENGLISH LESSONS: PROBLEMS AND PROSPECTS (Pedagogy of Higher and Secondary Education, 2009)
In this article the maintenance and structure of dialogical speech at lessons of English language as one of means of formation of the creative person of the schoolboy is considered.